2018
DOI: 10.1111/ppe.12518
|View full text |Cite
|
Sign up to set email alerts
|

Short interpregnancy intervals and adverse maternal outcomes in high‐resource settings: An updated systematic review

Abstract: Background Currently, no federal guidelines provide recommendations on healthy birth spacing for women in the United States. This systematic review summarises associations between short interpregnancy intervals and adverse maternal outcomes to inform the development of birth spacing recommendations for the United States. Methods PubMed/Medline, POPLINE, EMBASE, CINAHL, the Cochrane Database of Systematic Reviews, and a previous systematic review were searched to identify relevant articles published from 1 Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 62 publications
(145 reference statements)
0
65
2
2
Order By: Relevance
“…This manuscript is part of a theme issue on the Office of Population Affairs’ expert workgroup meeting on birth spacing and adverse pregnancy outcomes, which includes a separate summary of the overall meeting proceedings …”
Section: Introductionmentioning
confidence: 99%
“…This manuscript is part of a theme issue on the Office of Population Affairs’ expert workgroup meeting on birth spacing and adverse pregnancy outcomes, which includes a separate summary of the overall meeting proceedings …”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this systematic review is to summarise research on the associations between short interpregnancy intervals and adverse perinatal outcomes in high‐resource settings. The association between short interpregnancy intervals and adverse maternal outcomes in high‐resource settings is reported separately in this journal supplement . Findings from this review can be used to inform evidence‐based recommendations for healthy birth spacing for the United States .…”
Section: Introductionmentioning
confidence: 99%
“…The association between short interpregnancy intervals and adverse maternal outcomes in high-resource settings is reported separately in this journal supplement. 13 Findings from this review can be used to inform evidence-based recommendations for healthy birth spacing for the United States. 14 At present, although short interpregnancy interval is a recognised risk factor for preterm birth and low birthweight, 15,16 and the American College of Obstetricians and Gynecologists recommends women be advised to avoid interpregnancy intervals shorter than 6 months, 16 there are no federal recommendations on healthy birth spacing for the United States.…”
mentioning
confidence: 99%
“…The new reviews incorporated more narrow inclusion criteria by restricting included studies to those that defined short birth spacing using the interpregnancy interval (with short interpregnancy interval defined as some duration less than 24 months versus a well‐defined longer duration), controlled for at least maternal age (and socio‐economic position, for perinatal outcomes), and were conducted within countries categorised as “very high” on the United Nations Human Development Index . Details on the systematic review methodology, including study quality assessment, and the summary of evidence can be found in other manuscripts in this journal supplement . Studies employing a sibling comparison design, which compared differences in a woman's interpregnancy intervals and birth outcomes using a within‐woman analysis, were considered separately from the studies employing a conventional between‐women analysis.…”
Section: Evidence Presented On Short Interpregnancy Interval and Advementioning
confidence: 99%
“…47 Details on the systematic review methodology, including study quality assessment, and the summary of evidence can be found in other manuscripts in this journal supplement. 48,49 Studies employing a sibling comparison design, which compared differences in a woman's interpregnancy intervals and birth outcomes using a within-woman analysis, were considered separately from the studies employing a conventional between-women analysis.…”
Section: Systematic Reviewsmentioning
confidence: 99%